(untitled) (Research, Society and Development, 2021)
Objective: To describe the scientific evidence available in the national and international literature on the working conditions of health professionals during the Covid-19 pandemic. Method: integrative review, carried out in six electronic databases, being the database in Nursing, Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online, National Library of Medicine, SciVerse Scopus and Web of Science in the period of June and July 2020. Results: of the 596 articles found, only 02 were selected that answered the research question and the main working conditions evidenced were in relation to the reorganizations of the sectors within the Health Institution for the care of patients affected by Covid-19, excess load working hours, use of personal protective equipment for a long time and uncomfortable and situations that generate physical and emotional exhaustion. Conclusion: working conditions continue to be aggravated in the pandemic and require specific public actions.